Impact Point Dispersion Prediction for 300 mm R-Han 300 Artillery Rocket - Riyadl, Ahmad; Robertus Heru TriHarjanto; Pujo Widodo (Indonesian Journal of Aerospace, 2023)
The effectiveness of artillery rocket in battlefield is the determined by its impact point dispersion, which may occur due to manufacturing and measurement inaccuracy, initial launch perturbations and atmospheric conditions. Therefore, the objective of this study is to establish model that could predict the impact point dispersion of R-Han 300 rocket using Monte Carlo method. Generic rocket of 6 Degree-of-Freedom model was implemented to investigate the impact point. Initially two simulations with 1000 iterations were carried out, first to study the effect of value uncertainty of every parameter on the impact point dispersion at launch elevation angle 50 degrees, second to study the impact point dispersion caused by value uncertainty of all the parameters at launch elevation angles ranging from 30 to 70 degrees. The second simulation is then repeated with 10000 iterations. This study showed that the dispersion increases as the launch elevation angle increases, except around the optimal launch elevation angle that give the farthest range. Monte Carlo simulation with 10000 iterations showed a better normal distributed data then the simulation with 1000 iterations, but the maximum difference in value of CEP resulted from both simulations is very small, which is 3.16%.